Effect of moringa leaf powder supplementation on performance and antioxidant activity in broilers under heat stress: Moringa Leaf Powder Supplementation in Broilers under Heat Stress - VEDENDER .G P; VENKATESWARLU .M; NAGALAKSHMI .D; HARIKRISHNA .CH; PARASHURAMULU .S (Indian Journal of Poultry Science, 2025)
An experiment was conducted to investigate the effect of Moringa leaf powder supplementation on performance and antioxidant activity to alleviate heat stress in broilers during summer months. The experiment was conducted on 240 broiler chicks (Cobb-300) and randomly categorized into six dietary treatment groups with 8 replicates with 5 birds in each replicate (6×8×5). A corn-soy basal diet (BD) was prepared as a control and BD supplemented with chlortetracycline at 0.05% (BD-C), vitamin E at 0.025% (BD-E) and Moringa oleifera leaf powder (MLP) at 0.25% (BD-MLP-0.25), 0.5% (BD-MLP-0.5) and 0.75% (BD-MLP-0.75) of BD were prepared. MLP supplementation at 0.5% and 0.75% levels significantly improved (P<0.05) the overall growth performance and feed efficiency, without affecting feed consumption among all treatments. Nutrient retention, carcass parameters, visceral organs weights, humoral immunity and serum biochemical parameters were not influenced by dietary variations. MLP supplementation at 0.5% and 0.75% levels showed higher (P<0.05) antioxidant enzymes (superoxide dismutase and glutathione peroxidase) activity with significant reduction in lipid peroxidation. The lowest (P<0.05) levels of lipid peroxidation was noticed in broilers fed diets containing 0.75% MLP. Thus, present study indicates that addition of MLP at 0.50 and 0.75% to the broilers diets enhanced the growth and antioxidant enzymes activity in comparison to antibiotic and antioxidant (vitamin-E) supplementation. Thus it was concluded that dietary supplementation of MLP at 0.5% level is advised for ensuring better performance and improved antioxidant enzyme activity to minimize the heat stress in broilers throughout the summer.